PRESERVATION OF THE ANCIENT CANAL OF INDRAPATRA FORT: PELESTARIAN KANAL KUNO BENTENG INDRAPATRA - Aulia, Riski; Marduati; Ajis, Ambo A (Indonesian Journal of Islamic History and Culture, 2023)
This study aims to study the damage and preserving ancient canals of Indrapatra Fort, Aceh. This study uses archaeological research methods that are descriptive analysis, with data collection techniques using observation, interviews, and documentation studies. The results of the study show that Indrapatra Fort is a defensive building inherited from the Aceh sultanate that is estimated to have been built in the 16th century AD. Inside the Indrapatra Fortress Complex, there are canals or waterways that function to regulate the flow of water when a flood occurs. Archaeological technical studies found that the condition of the canal was mostly covered with earth. After excavations were carried out in August 2021, the condition of the canal was 70–80% damaged. The form of damage is broken, cracked, collapsed, crushed, and even shifted. Therefore, the authors hope that the local government and the community will protect and maintain the canal structure of Indrapatra Fort so that the structure can continue to exist in the community.